Photo- and electro-luminescence properties of phenothiazine/phenoxazine-functionalized pyrene-fused pyrazaacenes with aggregation-induced emission. (December 2022) - Wang, Chungui; Zhao, Yuling; Su, Ruige; Li, Debao; Guo, Yongchun; Su, Wenming; Yu, Tianzhi
Abstract: Two pyrene-fused pyrazaacenes containing phenothiazine and phenoxazine units, 10-(phenanthro[4, 5- abc ]phenazin-11-yl)-10 H -phenothiazine (Py-PTZ ) and 10-(phenanthro[4, 5- abc ]phenazin-11-yl)-10 H -phenoxazine (Py-PXZ ), were successfully synthesized and their thermal, optical and electronic properties were investigated systematically. Both of them are nearly non-emissive in chloroform solution but become highly emissive in the mixed solution of chloroform and n-hexane and in the solid states. The solution-processed doped devices with a structure of ITO/PEDOT:PSS (30 nm)/CBP:Py-PTZ or Py-PXZ (x wt%) (25 nm)/TPBi (35 nm)/Liq (2 nm)/Al (150 nm) were fabricated, in which the Py-PTZ -based doped device exhibited a maximum luminance (Lmax ) of 2570 cd/m 2, a maximum current efficiency (CEmax ) of 2.67 cd/A and a maximum external quantum efficiency (EQEmax ) of 1.64%, and the Py-PXZ -based doped device showed Lmax, CEmax and EQEmax of 4554 cd/m 2, 6.39 cd/A and 3.81%, respectively. Graphical abstract: Image 1 Highlights: Two pyrene-fused pyrazaacenes containing phenothiazine and phenoxazine units were successfully synthesized and characterized. These compounds exhibited AIE characteristics, and displayed strong red emission in thin solid films. The devices of the compound containing phenoxazine unit exhibited red emission with CEmax of 6.39 cd/A and EQEmax of 3.81%.